A Pilot Study Examining the Relationship among Crohn Disease Activity, Glucagon-Like Peptide-2 Signalling and Intestinal Function in Pediatric Patients - David L Sigalet; Dragan Kravarusic; Decker Butzner; Bolette Hartmann; Jens J Holst; Jon Meddings (Canadian Journal of Gastroenterology)
BACKGROUND/OBJECTIVES: The relationship between the enteroendocrine hormone glucagon-like peptide 2 (GLP-2) and intestinal inflammation is unclear. GLP-2 promotes mucosal growth, decreases permeability and reduces inflammation in the intestine; physiological stimulation of GLP-2 release is triggered by nutrient contact. The authors hypothesized that ileal Crohn disease (CD) affects GLP-2 release.